Social Media Use, Psychological Distress and Knowledge, Attitude, and Practices Regarding the COVID-19 Among a Sample of the Population of Pakistan - Rizwan, Muhammad; Ahmad, Tauseef; Qi, Xuehong; Murad, Manal Abdulaziz; Baig, Mukhtiar; Sagga, Abdullah Khalid; Tariq, Saba; Baig, Fizzah; Naz, Rozina; Hui, Jin (Frontiers in Medicine, 2021)
This study was conducted to assess social media (SM) use, psychological distress, and knowledge, attitude, and practices (KAP) regarding COVID-19 among a sample of the Pakistani population. An online cross-sectional study was conducted in Multan, Pakistan, between April and May 2020. Demographics details, SM use, psychological distress, and KAP on COVID-19 were investigated. A total of 800 respondents were analyzed, of which 33.5% (n=268) were females. No gender wise difference was found in terms of SM use and duration of SM use. Females were prone to have psychological disorders such as anxiety, depression, and stress than males in the current COVID-19 pandemic. The mean knowledge score of males was significantly higher compared to females (18.69±4.20vs.16.89±3.04, p<0.001), while the mean score of the attitude and practices on COVID-19 prevention measures were significantly better in females (p=0.012 and p<0.001, respectively). The psychological problems such as anxiety (p<0.001) and depression scores (p=0.033) were higher among females than males. The stress score was also higher in females but not significantly (p=0.079). The knowledge was significantly correlated with attitude, anxiety, depression, and stress. The regression analysis showed that Covid-19-related KAPs are the predictors of an individual's psychological suffering. The female gender was positively associated with anxiety and depression. The SM use was the predictor of the stress. In terms of SM use and duration, no gender differences were found. Females had higher levels of psychological issues such as anxiety, stress, and depression than males. Male respondents had significantly more knowledge of COVID-19 than female respondents, but females had significantly better attitudes and practiced COVID-19 prevention measures. Gender is a significant determinant of psychological distress and KAP about COVID-19. The government has already taken significant steps to limit the spread of the disease; however, much more effort is required to tackle this pandemic.